Proposta de plano de gerenciamento de resíduos sólidos para um provedor de internet - Lira, David Camilo Cavalcanti de (2018)
With population expansion and the need for supplies for human development, the population lacks measures that ease the generation of solid waste. The private initiative also enters into this responsibility, as reported in Law No. 12,305 of August 2010, making from this document the proposal of the Solid Waste Management Plan of the Internet Provider. Thus, assigning the correct classification, characterization and treatment of the waste and making fundamental factors for a new form of management, incorporating the principles of sustainability, that present problem solving and that allows transformations of situations of vulnerability. Therefore, it enables the good management of solid waste, which is an important way to avoid pollution to the environment and improve the quality of life of the population.